Therapeutic combination of catheter-directed thrombolysis, rheolytic thrombectomy and percutaneous transluminal angioplasty in acute on chronic limb ischemia: a case report - Erina Febriani Widiastari; Gary Pradhana; Marolop Pardede (Journal of Indonesia Vascular Access, 2022)
Background: Acute limb ischemia (ALI) is a sudden decrease in leg perfusion that threatens the viability of the limb with symptom onset within 2 weeks. In peripheral artery disease (PAD) conditions, occlusion of blood vessels can occur due to thrombosis or atherosclerotic plaque embolism, which is called "acute on chronic ischemia". The development of endovascular therapy has made this therapy an important role in restoring leg perfusion. The aim of this study to demonstrate the safety and feasibility of therapeutic combination of catheter-directed thrombolysis, rheolytic thrombectomy and percutaneous transluminal angioplasty in acute on chronic limb ischemia. Case Description: We report a case of a 51-year-old man, came to the hospital with complaints of pain in the left extremity that persisted at rest or activity and cold in the left extremity which has been felt since 2 weeks ago. A year ago, the patient started to feel pain in the left extremity that persist in activity. Physical examination revealed cold feet and muscle atrophy. Conclusion: Therapeutic combination of catheter-directed thrombolysis, rheolytic thrombectomy and percutaneous transluminal angioplasty are considered to be safe and feasible to do in acute on chronic limb ischemia.